Neural Tube Development - Donald Lowrie; Karen Marsh; Kyle Sliney; Bruce Giffin (Association of American Medical Colleges, 2010)
Abstract This web-based module provides clear, labeled animations of the significant tissues in central nervous system development of the embryo, starting with the completion of neurulation and including neural tube folding and elaboration of the brainstem, diencephalon, and telencephalon. The animations are based on both 3D models and 2D cross-sections. Users may rotate the 3D models, in addition to observing them change in chronological time within the narrated portion of the module. This work is the first of its kind, showing neural tube development in the embryo in both 3D and 2D animation. Based on user feedback, we incorporated more interactive opportunities with 3D embryo models and used a narration that is more conversational in quality.